Public health system - current status and world experience. - Andreyeva І. А.; Lugova О. V.; Nashyvanko О. V.; Chernyak, Yu. S.; Shevchenko О. А. (Medicni Perspektivi, 2016)
In the review, the evolution of Public Health and global development tendencies of Public Health system have been discussed. Stages of formation of the updated concept, principles of Public Health organization and the role of various organizations have been shown in the connection with development of the global concept of "Health for All". A well-functioning public health system is primarily the result of multisectoral cooperation. The aim of modern Public Health is to provide conditions of access to appropriate and cost-effective health care for all population groups, including health promotion and disease prevention.